THE EFFECT OF HABITS WATCHING ON SLEEP PATTERNS AND PHYSICAL FITNESS IN VOLLEYBALL ATHLETES - Gilang Aszi Gumilar; Alam Hadi kosasih; Z. Arifin; Azhar Ramadhana Sonjaya (Indonesian Journal of Physical Activity, 2025)
This study aims to analyze the effect of watching habits on sleep patterns and physical fitness among volleyball athletes at Gor DVB Bayongbong. The research employed a quantitative method with a pretest-posttest control group design involving 15 athletes. Instruments used were the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and the bleep test to measure physical fitness. The results show that watching habits significantly affect sleep patterns (Adjusted R Square 0.726), where higher watching intensity tends to reduce sleep quality. In addition, watching habits negatively affect physical fitness (Adjusted R Square 0.783). These findings highlight the importance of managing screen time to maintain both healthy sleep patterns and optimal physical fitness.